CA-MRSA em furunculose: relato de caso do sul do Brasil CA MRSA in furunculosis: case report of Southern Brazil - Fernanda Razera; Sabrina De Stefani; Renan Rangel Bonamigo; Gislaine Silveira Olm; Cícero Armídio Gomes Dias; Gabriel Azambuja Narvaez (Sociedade Brasileira de Dermatologia, 2009)
Staphylococcus aureus resistente à meticilina (MRSA), outrora isolado especificamente em ambientes hospitalares, vem sendo identificado como causador de infecções cutâneas em pacientes da comunidade. Neste artigo, é relatado um caso do sul do Brasil com furunculose por CA-MRSA. O microrganismo isolado foi submetido a exames de PCR para o gene mecA e para o gene que codifica a leucocidina de Panton-Valentine. Esses exames permitiram a identificação genotípica do CA-MRSA. Methicillin-resistant Staphylococcus aureus (MRSA), particularly isolated at hospital setting, has been identified in cutaneous infections of community patients. This paper reports a case of furunculosis from the southern Brazil. Dermatologists must be attentive to this emergent etiological diagnosis. The isolated microorganism was subjected to PCR for gene mecA and to PCR for the gene that encodes the leukocidin of Panton-Valentine. These exams enabled genotypic identification of CA-MRSA.